Customer Path 5A Relations to the Utilization of Dental and Oral Health Services - Eka Yunila Fatmasari; Dwi Windu Kinanti Arti; Wulan Kusumastuti; Putri Asmita Wigati; Khoerunnisak Khoerunnisak (Universitas Aisyah Pringsewu, 2022)
The decrease in outpatient visits at The Dental and Oral Hospital at RSGM UNIMUS occurred in 2020. The limited number of human resources, restrictions on community activities due to the pandemic, and unstructured marketing activities became obstacles in bringing in patient candidates. The purpose of this study is to analyze the relationship between the paths of customer behavior towards a brand consisting of awareness, appeal, asking, acting, and advocating for the use of dental and oral health services. This research is an observational quantitative research with a cross-sectional approach. The sample in this study was 100 respondents with an accidental sampling technique. Data were analyzed using the chi-square test. The results showed a relationship between awareness, appeal, asking, acting, and advocating using dental and oral health services with the same p-value of 0.000. It is expected that RSGM UNIMUS can manage marketing activities in a more planned and structured way starting from the design of service flow content and service facilities clearly and understandably, monitoring and periodic evaluation of each uploaded content, establishing collaboration with UNIMUS dental students as a network and strengthening the function of the marketing team in increasing cooperation with health insurance to increase patient visits. Abstrak: Penurunan kunjungan rawat jalan di RSGM Unimus terjadi di tahun 2020. Keterbatasan jumlah sumber daya manusia, pembatasan kegiatan masyarakat akibat pandemi, serta kegiatan pemasaran yang belum terstruktur menjadi kendala dalam mendatangkan calon pasien. Tujuan penelitian ini untuk menganalisis hubungan jalur perilaku pelanggan terhadap sebuah brand yang terdiri dari aware, appeal, ask, act, dan advocate terhadap pemanfaatan pelayanan kesehatan gigi dan mulut. Penelitian ini merupakan penelitian kuantitatif observasional dengan pendekatan cross sectional. Sampel dalam penelitian ini sebesar 100 responden dengan teknik pengambilan sampel accidental sampling. Data dianalisis dengan menggunakan uji chi-square. Hasil penelitian menunjukkan terdapat hubungan antara aspek aware, appeal, ask, act, dan advocate dengan pemanfaatan pelayanan Kesehatan Gigi dan Mulut dengan p-value yang sama yaitu 0,000. Diharapkan RSGM Unimus dapat mengelola kegiatan pemasaran lebih terencana dan terstruktur mulai dari desain konten alur pelayanan dan fasilitas pelayanan secara jelas dan dapat dipahami, monitoring dan evaluasi berkala pada setiap konten yang sudah di upload, menjalin kerjasama mahasiswa kedokteran gigi Unimus sebagai jejaring dan menguatkan fungsi dari tim pemasaran dalam meningkatkan kerjasama dengan asuransi kesehatan untuk meningkatkan kunjungan pasien.